Impacts of climate change on key soil ecosystem services and interactions in Central Asia. (September 2020) - Li, Jiangyue; Chen, Hongxing; Zhang, Chi
Highlights: Climate projections in Central Asia showed trends toward warmer and wetter conditions from 2021 to 2060. The average soil conservation and sand fixation in Central Asia were projected to increase. Wind speed and temperature have apparent effects on sand fixation. Precipitation is an important factor affecting soil conservation and net primary productivity. Abstract: In Central Asia (CA), climate change influences soil ecosystem services (ESs) that are essential for the sustainable management of natural resources and development of social economies. Based on the Revised Universal Soil Equation (RUSLE), Revised Wind Erosion Equation (RWEQ) and Carnegie-Ames-Stanford Approach (CASA), we simulated the three key ESs, including soil conservation (SC), sand fixation (SF) and net primary productivity (NPP), in CA for two future periods (2030s and 2050s) using a climate projection for two representative concentration pathway (RCP) scenarios: RCP 2.6 and RCP 8.5. Based on the Inter-sectoral Impact Model Inter-comparison Project (ISIMIP2b) climate model, a consensus was found using the two RCP scenarios, and it indicated that an increase in temperature (average: 1.48 °C–3.59 °C) and increase in rainfall (average: 5.07 mm–33.79 mm) would occur among the four climatic subregions under future climate changes. The SC and SF were projected to increase by 4.85%–29.14% and 35.14%–161.25% under RCP 2.6 and RCP 8.5, respectively. The results indicated that the non-phreatophyte shrubland distributed in the central arid desert shrub area would decrease by 5.2 g C/m 2 –15.94 g C/m 2 . Correlation analysis indicated a positive relationship between the difference in SC and NPP (R = 0.54–0.64), except in the humid and cold forest-meadow area in Tianshan, where negative correlations existed between the difference in SF and NPP (R = −0.07 to −0.58)/SC (R = −0.21 to −0.48) from 1986 to 2060. Climatic changes are the major drivers of ecosystem service fluctuations. A correlation analysis showed that the decrease in precipitation significantly hindered SC (R = 0.37–0.69) and NPP (R = 0.45–0.74), while the increases in wind speed (R = 0.45–0.85) and temperature (R = 0.29–0.69) exerted obvious positive influences on SF. Our research results show that risks of vegetation degradation will occur in the middle arid desert shrub area, and ecological restoration projects (e.g. ecological reserve) should be established to improve soil ESs efficiency.